Clinical findings in 39 individuals with Bohring–Opitz syndrome from a global patient‐driven registry with implications for tumor surveillance and recurrence risk. Issue 4 (7th February 2023) - Russell, Bianca E.; Kianmahd, Rebecca R.; Munster, Chelsea; Yu, Anna; Ahad, Leena; Tan, Wen‐Hann
Abstract: Bohring–Opitz syndrome (BOS) is a rare genetic condition caused by pathogenic variants in ASXL1, which is a gene involved in chromatin regulation. BOS is characterized by severe intellectual disabilities, distinctive facial features, hypertrichosis, facial nevus simplex, severe myopia, a typical posture in infancy, variable anomalies, and feeding issues. Wilms tumor has also been reported in two individuals. We report survey data from the largest known cohort of individuals with BOS with 34 participants from the ASXL Patient‐Driven Registry and data on five additional individuals with notable findings. Important or novel findings include hepatoblastoma ( n = 1), an additional individual with Wilms tumor, two families with a parent who is mosaic including a pair of siblings, birth weights within the normal range for the majority of participants, as well as presence of craniosynostosis and hernias. Data also include characterization of communication, motor skills, and care level including hospitalization frequency and surgical interventions. No phenotype–genotype correlation could be identified. The ASXL Registry is also presented as a crucial tool for furthering ASXL research and to support the ASXL community.